Seaborne perils: piracy, maritime crime, and naval terrorism in Africa, South Asia, and Southeast Asia - Elleman, Bruce A. (Rowman & Littlefield, 2018)
Historical piracy and its impact -- Early attempts to fight piracy -- Piracy during the Taiping Rebellion and the Arrow War -- State-sponsored piracy in the Taiwan Straits -- The pirating of Vietnamese boat people -- Confronting maritime crime in Australian waters -- Twenty-first century high seas piracy off of Somalia -- Maritime crime and piracy in Southeast Asia and the South China Sea -- Piracy and maritime terrorism -- Successes and failures of counter-piracy operations -- Conclusions: international piracy in the era of global maritime domain awareness